Inactivation of autophagy ameliorates glucocorticoid-induced and ovariectomy-induced bone loss - Lin, Neng-Yu; Chen, Chih-Wei; Kagwiria, Rosebeth; Liang, Ruifang; Beyer, Christian; Distler, Alfiya; Luther, Julia; Engelke, Klaus; Schett, Georg; Distler, Jörg (Annals of the Rheumatic Diseases, 2016)
Autophagy has recently been shown to regulate osteoclast activity and osteoclast differentiation. Here, we aim to investigate the impact of autophagy inhibition as a potential therapeutic approach for the treatment of osteoporosis in preclinical models.Systemic bone loss was induced in mice by glucocorticoids and by ovariectomy (OVX). Autophagy was targeted by conditional inactivation of autophagy-related gene 7 (Atg7) and by treatment with chloroquine (CQ). Bone density was evaluated by microCT. The role of autophagy on osteoclastogenesis was analysed by osteoclastogenesis and bone resorption assays. The quantification of receptor activator of nuclear factor ? B ligand and osteoprotegerin proteins in cocultures was performed using ELISA whereas that of osteoclast and osteoblast differentiation markers was by qPCR.Selective deletion of Atg7 in monocytes from Atg7(fl/fl)_x_LysM-Cre mice mitigated glucocorticoid-induced and OVX-induced osteoclast differentiation and bone loss compared with Atg7(fl/fl) littermates. Pharmacological inhibition of autophagy by treatment with CQ suppressed glucocorticoid-induced osteoclastogenesis and protected mice from bone loss. Similarly, inactivation of autophagy shielded mice from OVX-induced bone loss. Inhibition of autophagy led to decreased osteoclast differentiation with lower expression of osteoclast markers such as NFATc1, tartrate-resistant acid phosphatase, OSCAR and cathepsin K and attenuated bone resorption in vitro. In contrast, osteoblast differentiation was not affected by inhibition of autophagy.Pharmacological or genetic inactivation of autophagy ameliorated glucocorticoid-induced and OVX-induced bone loss by inhibiting osteoclastogenesis. These findings may have direct translational implications for the treatment of osteoporosis, since inhibitors of autophagy such as CQ are already in clinical use.
EVALuna2:10103